2020
DOI: 10.3390/microorganisms8122028
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of 33 Bacillus cereus sensu lato Isolates from Agricultural Fields from Eleven Widely Distributed Countries by Whole Genome Sequencing

Abstract: The phylogeny, identification, and characterization of 33 B. cereus sensu lato isolates originating from 17 agricultural soils from 11 countries were analyzed on the basis of whole genome sequencing. Phylogenetic analyses revealed all isolates are divided into six groups, which follows the generally accepted phylogenetic division of B. cereus sensu lato isolates. Four different identification methods resulted in a variation in the identity of the isolates, as none of the isolates were identified as the same sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 38 publications
(74 reference statements)
1
6
1
Order By: Relevance
“…Bioinformatic analysis of the genome showed that the types of proteases and peptidases encoded by the three bacteria were similar, whereas the genes encoding for enzymes responsible for gluten degradation remained unclear. The genome size, GC content and genes with coding sequences of the three B. cereus strains (Table S1) in the present study were similar to those of previously reported B. cereus strains [35]. Genomic information provides insights into the mechanisms of bacteria, and the genome analysis of Chryseobacterium taeanense sp.…”
Section: Discussionsupporting
confidence: 87%
“…Bioinformatic analysis of the genome showed that the types of proteases and peptidases encoded by the three bacteria were similar, whereas the genes encoding for enzymes responsible for gluten degradation remained unclear. The genome size, GC content and genes with coding sequences of the three B. cereus strains (Table S1) in the present study were similar to those of previously reported B. cereus strains [35]. Genomic information provides insights into the mechanisms of bacteria, and the genome analysis of Chryseobacterium taeanense sp.…”
Section: Discussionsupporting
confidence: 87%
“…In this work, we provide strong evidence indicating that light directly modulates the quorum network in A. baumannii . We focused on motility and biofilms formation, which are different bacterial processes shown to depend on quorum sensing 4 7 , and are modulated by light 14 . As has been extensively described, our results also show that AbaI is involved in these responses.…”
Section: Discussionmentioning
confidence: 99%
“…Quorum sensing (QS) has been shown to modulate bacterial collective behaviors such as biofilm formation, motility, virulence, and even drug resistance mechanisms in a number of bacteria including A. baumannii 4 7 . Quorum sensing is a cell–cell communication system employed by bacteria to coordinate the expression of specific genes as a function of population density.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the limited number of available Rhodococcus genomes, the exact ANI threshold for species affiliation is not certain. It has been seen on other bacterial groups (e.g., the Bacillus cereus group [39], the genus Serratia [40]) that this threshold ranges between 92 and 96%. Based on the topology of both the 16S rRNA sequences and the whole-genome comparison, USK10 can be definitely placed and is well supported within the Rhodococcus genus.…”
Section: Phylogenetic Placement Of Rhodococcus Sp Usk10mentioning
confidence: 99%